(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to highlight the importance of time-oriented resource consumption accounting technology in achieving marketing leadership, as the researcher used the inductive method in the theoretical aspect by conducting a survey of studies that presented the research variables with the aim of extracting ideas and compiling the theoretical foundations presented in books, theses, dissertations and local, Arab and foreign periodicals and using the analytical method in the practical aspect in linking between the research variables, and the research reached the most important results: - Time-oriented resource consumption accounting technology leads to the achievement of marketing leadership, in addition to enhancing the competitiveness of the economic unit.